I stink! - McMullan, Kate.; McMullan, Jim, 1936-2019. (New York : Joanne Cotler Books, 2002)
A big city garbage truck makes its rounds, consuming everything from apple cores and banana peels to leftover ziti with zucchini.
Keywords: Refuse and refuse disposal -- Fiction